Adelopsis diabolica, a new species of Ptomaphagini (Coleoptera: Leiodidae: Cholevinae) from São Paulo State, Brazil - Gomyde, Eduardo C.; Gnaspini, Pedro (Zootaxa, 2019)
Adelopsis diabolica, new species (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) is described from Boracéia Biological Station, São Paulo State, Brazil. The apex of the male aedeagus is uniquely armed and diagnostic. Females have slightly expanded protarsomeres (less expanded than those of males), a very rare feature in the family.